First report on in-depth genome and comparative genome analysis of a metal-resistant bacterium Acinetobacter pittii S-30, isolated from environmental sample - Singh, Rajnish Prakash; Sinha, Ayushi; Deb, Sushanta; Kumari, Kiran (Frontiers in Microbiology, 2024)
A newly isolated bacterium Acinetobacter pittii S-30 was recovered from waste-contaminated soil in Ranchi, India. The isolated bacterium belongs to the ESKAPE organisms which represent the major nosocomial pathogens that exhibit high antibiotic resistance. Furthermore, average nucleotide identity (ANI) analysis also showed its closest match (>95%) to other A. pittii genomes. The isolate showed metal-resistant behavior and was able to survive up to 5 mM of ZnSO4. Whole genome sequencing and annotations revealed the occurrence of various genes involved in stress protection, motility, and metabolism of aromatic compounds. Moreover, genome annotation identified the gene clusters involved in secondary metabolite production (BGCs) such as arylpolyene, acinetobactin like NRP-metallophore, betalactone, and hserlactone-NRPS cluster. The metabolic potential of A. pittii S-30 based on COG, and KEGG indicated a high number of genes related to stress protection, metal resistance, and multiple drug-efflux systems etc, which is relatively rare in A. pittii strains. Additionally, the presence of various CAZymes such as glycoside hydrolases (GHs), glycosyl transferases (GTs), and other genes associated with lignocellulose breakdown suggests that strain S-30 has strong biomass degradation potential. Furthermore, an analysis of genetic diversity and recombination in A. pittii strains was performed to understand the population expansion hypothesis of A. pittii strains. To our knowledge, this is the first report demonstrating the detailed genomic characterization of a heavy metal-resistant bacterium belonging to A. pittii. Therefore, the A. pittii S-30 could be a good candidate for the promotion of plant growth and other biotechnological applications.